Penurunan Total Tanin Silase Semak Bunga Putih (Chromolaena odorata) dengan Aditif Tepung Putak (Coryphaelata robx) dan Isi Rumen Sapi - muhammad ridla; Yelly Magdalena Mulik; Iwan Prihantoro; Marthen Luther Mullik (Faculty of Animal Science, Universitas Gadjah Mada, 2016)
This study was aimed to assess the effect of the addition of putak meal (as a source of carbohydrates) and rumen content (as a source of enzymes) in the making of C. odorata silage to the total content of tannins and nutrient content of C. odorata silage. The treatments were: CO (C. odorata), COP (C. odorata + 10% of putak meal), COPR5 (C. odorata + 10% of putak meal + 5% of rumen content), and COPR10 (C. odorata + 10% of putak meal + 10% of rumen content). The experimental design used was Completely Randomized Design, with 4 x 2 factorial patterns. The first factor was the treatment (CO, COP, COPR4, COPR10) and the second factor is the silage fermentation time (0 days and 21 days). Each treatment was replicated 4 times. The variables measured were concentration of total tannin content and nutrient content. The results showed that the addition of (10% of putak meal and 10% of rumen content) decrease total tannins of the silage by 15.50%. The nutrient content (OM and OP) increased by 3.45% and 41.81% respectively as well as a decline in crude fiber 3% when compared to the silage without additives. Fermentation time of C. odorata silage for 21 days produced the best quality silage fermentation time compared to 0 days.